Synergistic effect of Ru embedded 2D Ti3AlC2 binary cocatalyst with porous g-C3N4 to construct 2D/2D Ru-MAX/PCN heterojunction for enhanced photocatalytic H2 production - Tahir, Beenish (Elsevier Ltd, 2021)
Developing engineering advanced semiconductor materials with low cost and high efficiency have great importance in solar assisted hydrogen production. In this work, well-designed Ru modulated oxygen defective Ti3AlC2 MAX multilayers binary cocatalyst with porous g-C3N4 has been fabricated through ultrasonic approach. Synergistic effect of Ru/Ti3AlC2 enabling proficient charge carrier transportation for significantly enhanced H2 production. The optimized 3Ru-15Ti3AlC2/g-C3N4 exhibited 1445 µmol g-1h-1 of H2 evolution rate which is 7.67 and 16.35 times more than using 15Ti3AlC2/CN and CN samples. The obvious augmented H2 production can be attributed to efficient charges separation with higher light absorption due to Ru/Ti3AlC2 binary cocatalyst. The catalyst loading and sacrificial reagents further confirms mass transfer and surface-active sites exposed to light irradiation. This study provides new approach to construct heterojunction of 2D/2D self-assembly, enabling synergistically improved quantum yield with higher cyclic stability and can be further explored in other solar energy assisted applications.